2014
DOI: 10.1097/jcp.0000000000000056
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Venlafaxine on Cortical Motor Area Activity in Healthy Subjects

Abstract: In the study, we used functional magnetic resonance imaging associated with behavioral assessment to observe the effects of venlafaxine on the modulation of human motor cortex activation and to provide preliminary data for further assessing its influence on motor functional reorganization after stroke injury. In a randomized, double-blind, crossover study, 8 right-handed subjects received 75 mg of either venlafaxine or a placebo daily over a period of 7 days separated by 3 washout days. The volunteers were ask… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
6
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 24 publications
(15 reference statements)
1
6
0
Order By: Relevance
“…Hence, we do not consider the small changes in Erb's point latencies to be meaningful. Venlafaxine also decreased the spinal Cv7 latency, which could imply an increased neuronal excitability and improved motor response, as has been shown previously in a functional magnetic resonance imaging study . Oxycodone, on the other hand, did not change any of the parameters of spinal EPs.…”
Section: Discussionsupporting
confidence: 80%
“…Hence, we do not consider the small changes in Erb's point latencies to be meaningful. Venlafaxine also decreased the spinal Cv7 latency, which could imply an increased neuronal excitability and improved motor response, as has been shown previously in a functional magnetic resonance imaging study . Oxycodone, on the other hand, did not change any of the parameters of spinal EPs.…”
Section: Discussionsupporting
confidence: 80%
“…On the other side, earlier preliminary studies and a recent meta-analysis confirmed that selective serotonin reuptake inhibitors improve motor recovery after stroke, even in people who were actually not depressed [15] , [16] . In a randomized, double blind, crossover study 1 week treatment with VLX significantly improved finger-tapping rate, a motor task compared to placebo [17] . This improvement showed positive correlation with the activation of sensory and motor cortical areas caused by the drug [17] .…”
Section: Introductionmentioning
confidence: 94%
“…In a randomized, double blind, crossover study 1 week treatment with VLX significantly improved finger-tapping rate, a motor task compared to placebo [17] . This improvement showed positive correlation with the activation of sensory and motor cortical areas caused by the drug [17] .…”
Section: Introductionmentioning
confidence: 94%
“…Previous studies have proposed that venlafaxine improves attention, motor activity, and response time . To observe the effects of venlafaxine on the human motor cortex, a study using fMRI in combination with different motor tasks showed that one‐week treatment improved the finger‐tapping rate and increased the activations of contralateral primary sensorimotor cortex, contralateral premotor cortex, and contralateral supplementary motor area . On the other hand, the authors found the activation of the parietal cortices was decreased.…”
Section: Discussionmentioning
confidence: 99%